Luce Irigaray (2012). Meryem'in Esrarı (Le Mystére deMarie) (Çev. Feyan Yıldırım). İstanbul: Pinhan Yayıncılık(47 sayfa). ISBN: 978-605-5302-09-2 - (:unkn) unknown (My University, 2014)
0
Keywords: Sosyoloji